Uji Laboratorium: Analisis Berat Lumpur Pemboran Pada Sumur Can - Wahyuni, Viola Sri; Fathan, Muhammad Rizqie; Ulfah, Baiq Maulinda (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Drilling mud plays an important role in maintaining well stability, especially since each trajectory faces different lithological and formation pressure issues. On the 36